Students’Self- Strategies in Memorizing English Vocabulary: Survey Study at Ponpes Al-Muwahhidin Lelede - Tawali, Tawali (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This research aimed to analysis the student’s self-strategies in memorizing English Vocabulary survey study at Ponpes Al-Muwahhidin Lelede. The subject of this research was first grade VII-A of MTs Al-Muwahhidin in academic year 2022/2023. The sample of this study were 7 students. The method of this research was qualitative survey study. The technique of data collection applied in this study were interview, recording and documents. Then the procedure of data analysis was data condensation, data display and conclusion drawing and verification used the theory of Miles and Huberman 2014. The result of this research, the researcher found out the types of student’s strategies in memorizing English vocabulary. The strategies used by the students were making note strategy, repeating strategy, singing strategy and practice strategy. Therefore, the strategies used by students to remember the meaning and spelling were practice strategy, writing strategy, memorizing strategy and reading strategy.